Loose-patch clamp analysis applied to voltage-gated ionic currents following pharmacological ryanodine receptor modulation in murine hippocampal cornu ammonis-1 pyramidal neurons - Bertagna, Federico; Ahmad, Shiraz; Lewis, Rebecca; Silva, S. Ravi P.; McFadden, Johnjoe; Huang, Christopher L.-H.; Matthews, Hugh R.; Jeevaratnam, Kamalan (Frontiers in Physiology, 2024)
Introduction. The loose-patch clamp technique was first developed and utilized in native amphibian skeletal muscle (SkM), offering useful features complementing conventional sharp micro-electrode, gap or conventional patch voltage clamping. It demonstrated feedback effects of pharmacological modification of ryanodine receptor (RyR) mediated Ca2+ release on the Na+ channel (Nav1.4) currents initiating excitation-coupling in native murine SkM. Effects of the further, RyR and Ca2+-ATPase (SERCA), antagonists, dantrolene and cyclopiazonic acid (CPA), additionally implicated background tubular-sarcoplasmic Ca2+ domains in these actions. Materials and Methods. We extend the loose-patch clamp approach to ion current measurements in murine hippocampal brain slice cornu ammonis-1 (CA1) pyramidal neurons. We explored effects on Na+ currents of pharmacologically manipulating RyR and SERCA-mediated intracellular store Ca2+ release and re-uptake. We adopted protocols previously applied to native skeletal muscle. These had demonstrated Ca2+-mediated feedback effects on Na+ channel function. Results. Experiments applying depolarizing 15 ms duration loose patch clamp steps to test voltages -40 to 120 mV positive to the resting membrane potential demonstrated that 0.5 mM caffeine decreased inward current amplitudes agreeing with the previous SkM findings. It also decreased transient but not prolonged outward, current amplitudes. However, 2 mM caffeine affected neither inward nor transient outward but increased prolonged outward currents, in contrast to its increasing inward currents in SkM. Furthermore, similarly, also in contrast to, previous SkM findings, both dantrolene (10 μM) and CPA (1 μM) pre-administration left both inward and outward currents unchanged. Nevertheless, dantrolene pretreatment still abrogated the effects of subsequent 0.5-and 2-mM caffeine challenge on both inward and outward currents. Finally, CPA abrogated the effects of 0.5 mM caffeine on both inward and outward currents but with 2 mM caffeine, inward and transient outward currents were unchanged but sustained outward currents increased. Conclusions. We thus extend loose-patch clamping in establishing pharmacological properties of murine CA1 pyramidal neurons and their similarities and contrasts with SkM. Here, evoked though not background Ca2+ -store release influenced Nav and Kv excitation consistent with smaller contributions of background store Ca2+ release to resting [Ca2+ ]. This potential noncanonical mechanism could modulate neuronal membrane excitability or cellular firing rates.